Magnetic resonance imaging and shear wave elastography comparison in the evaluation of breast lesions - Süt, Suat Kamil; Ağlamış, Serpil; Üçer, Özlem (My University, 2022)
This study aims to compare the Magnetic Resonance Imaging (MRI) and Shear Wave Elastography (SWE) data and investigate their contribution to diagnosis when both are individually used and combined. This study included the consent of 46 diagnostic biopsy patients after their breast MRI examination was performed. Mass appearance patients in the sonographic evaluation were SWE examined before the biopsy. In MR examination, lesion localization, size, contrast curves, contrast enhancement features, intensity in the fat-suppressed T2A sequence, Emean value in SWE examination, and histopathological results were examined. Individual and combined use of MRI and SWE findings were evaluated with histopathological results. The diagnosis consistency was compared according to the histopathological results of the malignant-benign defined lesions. Higher sensitivity in MRI; higher specificity and accuracy in SWE were acquired when both methods were compared. The accuracy of MRI improved when MRI use is combined with SWE. The combined use of SWE with MRI increases the diagnostic accuracy in breast lesion characterization. We observed that lesions showing a type 3 enhancement curve and iso-hypointense on the T2W sequence in breast MRI could be predicted to show a stiff elasticity pattern on SWE due to higher elastography values.
Keywords: Kadın Hastalıkları ve Doğum; Patoloji; Nörolojik Bilimler; Onkoloji; Sağlık Bilimleri ve Hizmetleri